2018
DOI: 10.3846/jbem.2018.5563
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry in the Stock Price Response to Macroeconomic Shocks: Evidence From the Korean Market

Abstract: This study investigates stock price movements in response to macroeconomic shocks, allowing for asymmetry in this relationship. Given Ferson’s (1989) finding that large and small stocks can exhibit different risk behaviors, we examine the behaviors of the KOSPI and KOSDAQ stock markets in response to changes in the price level, real interest rate, and real USD/KRW exchange rate using simple and nonlinear autoregressive-distributed lag (ARDL) models. We find that the long-run effects of macroeconomic shocks are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 64 publications
2
10
0
Order By: Relevance
“…Signs of nonlinearity have also been reported in several studies (see, e.g., Lardic and Mignon, 2008;Zhang, 2017). A recent study by Lee and Ryu (2018) shows that stock price shocks respond insignificantly to macroeconomic variables under simple ARDL, whereas a significant and negative long-run effect is found for almost every explanatory variable, a market pair under the nonlinear model. The nonlinear ARDL is also used in Alqaralleh (2020), in which the author highlights that responses of stock return to macroeconomic variables are generally asymmetric.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Signs of nonlinearity have also been reported in several studies (see, e.g., Lardic and Mignon, 2008;Zhang, 2017). A recent study by Lee and Ryu (2018) shows that stock price shocks respond insignificantly to macroeconomic variables under simple ARDL, whereas a significant and negative long-run effect is found for almost every explanatory variable, a market pair under the nonlinear model. The nonlinear ARDL is also used in Alqaralleh (2020), in which the author highlights that responses of stock return to macroeconomic variables are generally asymmetric.…”
Section: Introductionsupporting
confidence: 58%
“…The issue of incorporating nonlinearity in the relationship between the aggregate stock price level and the macroeconomic variables in an empirical analysis has received considerable critical attention. Drawing on the seminal papers (among others; Yang et al 2018;Lee and Ryu, 2018;Han et al, 2012;Lee and Ryu, 2013) that highlight the asymmetric response of stock returns to related macroeconomic variables, we see that different variables have been found n previous studies to be included in order to empirically investigate this relationship. This study uses the following general specification:…”
Section: The Economic Modelmentioning
confidence: 90%
“…Volatility dynamics are an on-going hot research topic in the field of economics (Kim, Park, and Ryu, 2018 [24]; Ryu, 2015a, 2015b [25,26]; Chun, Cho, and Ryu, 2019, 2020 [27,28]; Ryu, 2014a, 2014b [29,30]). For example, some previous studies analyze the relationship between volatility movements and economic factors in financial markets (Shim, Kim, Kim, and Ryu, 2015 [31]; Lee and Ryu, 2018 [32]; Lee and Ryu, 2019 [33]). Other studies examine the return and volatility transmissions between related markets (Guo, Han, Liu, and Ryu, 2013 [34]; Kim, Ryu, Seo, 2015 [35]; Lee, Kang, and Ryu, 2015 [36]; Lee and Ryu, 2016 [37]; Lee, Lee, and Ryu, 2019 [38]).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lee and Ryu [26] found that the macroeconomic indicators do not affect when analyzed with the linear model, while all the macroeconomic indicators influence the stock market when an analysis was performed using a nonlinear model.…”
Section: Literature Reviewmentioning
confidence: 99%